Legal Protection For Vulnerable Workers in The Labor Social Security System in Order to Increase The Participation of Social Security: A Case Study of Padang City - Khairani, Khairani; Darnis, Darnis; Lubis, Ikhsan; Oktaviandra, Surya; Mardiah, Ainul (Magister of Law, Faculty of Law, University of Mataram, 2025)
Vulnerable workers, often engaged in informal sectors with low and unstable incomes, face significant barriers in accessing employment-based social security programs. In the social security system, according to Law No.40/2004 and Law No.24/2011 who are social security participants are independent participants, wage recipients and contribution recipients (poor people, while informal workers are not mentioned as participants covered by the Government. This article aims to find out how social security protection is for informal workers and who is responsible for the payment of their membership contributions as social security participants. Using an empirical legal research method, the study analyzes the implementation of social security policies at the local level, particularly initiatives to include informal workers such as fishermen, religious educators, and ride-hailing drivers. Data were collected through field observation, interviews with relevant stakeholders, and review of secondary legal documents. The study reveals that local government initiatives play a critical role in expanding enrollment, particularly through targeted identification of eligible workers and the allocation of public budget to subsidize premiums. The novelty of this research lies in its focus on subnational policy implementation and the mechanisms through which local governments operationalize inclusive social protection. The findings highlight how coordination between central and local authorities contributes to expanding access to social security and reducing socioeconomic vulnerability among informal labor groups. This study offers practical insights for policymakers seeking to close protection gaps and achieve broader coverage in employment-based social security systems.